Implementation of virtual reality to enhance spatial abilities: a study on aspects, effects, and differences in participants' initial ability levels - Pahmi, Samsul; Vrapi, Asllan; Supriyadi, Edi (International Journal of Didactic Mathematics in Distance Education, 2024)
The rapid advancement of Virtual Reality (VR) technology presents a timely opportunity to enhance spatial abilities—skills fundamental to success in various educational and professional domains. This study addresses the urgent need to understand how VR can be effectively utilized in educational contexts to support spatial skill development. Employing a Systematic Literature Review (SLR) methodology, this research synthesizes findings from 26 peer-reviewed studies published between 2013 and 2022, sourced from Scopus, ScienceDirect, and SAGE Journals. The objectives are threefold: (1) to assess the effectiveness of VR in improving spatial abilities, (2) to identify at least three key factors influencing VR’s impact, and (3) to examine how initial spatial ability levels affect learning outcomes. The findings reveal that VR significantly enhances spatial skills, particularly mental rotation, and is most beneficial for learners with initially low spatial ability. Furthermore, three primary factors affecting VR effectiveness are identified: the level of interactivity, task alignment with learning objectives, and user immersion. From an affective perspective, VR also increases learner motivation and engagement, driven by its immersive and realistic environment. This research contributes to the growing body of knowledge on educational technology by offering evidence-based insights into the conditions under which VR can be most effective. The findings hold practical implications for educators, curriculum designers, and technology developers aiming to design targeted interventions for spatial skill development using VR.